Beyond the surface of capacity building: a mixed-methods study of the core functions and forms of dissemination and implementation science consultations - Kera N. Swanson; Nicole A. Stadnick; Gregory A. Aarons; Lauren Brookman-Frazee; Isaac Bouchard; Zeying Du; Anna G. Brubaker; Carrie Geremia; Kelli Cain; Lilliana R. Conradi; Marisa Sklar; Clare Viglione; et al. (Implementation Science Communications)
Abstract Background The number of Dissemination and Implementation Science (DIS) capacity building programs is increasing worldwide. These programs aim to enhance diverse DIS skills through a variety of activities. Our team’s systematic review of DIS programs determined that DIS consultations were offered across 67% of programs, yet their specific roles in capacity development were not well defined. This mixed methods study aimed to identify and categorize the functions and forms of consultation activities across three DIS capacity building programs at the University of California San Diego that varied in content focus and infrastructure and then to map findings onto DIS competencies. Methods Consultation notes from the three programs were extracted for content analysis to identify discussion topics, DIS guidance provided, and resources shared. Generative artificial intelligence (ChatGPT Plus) facilitated content analyses with multiple rounds of validation from program consultants to refine and finalize themes. Themes were categorized into consultation functions and forms. Forms were mapped onto DIS competencies and a gap analysis was conducted to identify areas for improvement. Program metrics were used to further contextualize findings. Results A total of 108 consultation notes were analyzed across the three programs. The most common types of support requested related to grant proposals (54%) and ongoing D&I projects (25%). Consultation discussion topics most frequently involved applying implementation science principles (55%) grant development (31%), guidance centered on DIS methods (47%), and study/project design (37%). Consultation guidance was most often aligned with intermediate-level DIS competencies (58%), primarily in the design and analysis and practice-based considerations domains. Conclusions These findings highlight the nature of DIS consultation services, particularly among those seeking support for grant proposals and ongoing implementation projects. Consultations primarily addressed intermediate-level competencies within the domains of design, analysis, and practice-based implementation strategies, indicating a clear opportunity to strengthen support for both foundational and advanced skill development. These results suggest the need for scalable consultation frameworks, improved tracking systems, and tiered training resources to optimize the reach and impact of DIS capacity-building efforts.